A comparative study on removal of basic violet 10 by adsorption and photocatalytic degradation using low cost activated carbon. (1st January 2013) - Ravichandran, P.; Sowmya, A.; Meenakshi, S.
This study compare the adsorption and photodegradation methods for the removal of basic violet 10 (BV) dye. Adsorption studies were carried out using activated carbon prepared from rice husk (RC). The photocatalytic degradation reactions using RC + TiO2 mixture were carried out under UV irradiation. The inﬂuence of operating parameters governing dye removal such as contact time, pH and effect of dose, adsorption isotherms and kinetics were investigated. The negative ΔGº values revealed that the dye removal process is spontaneous. The percentages of dye removal using TiO2 /UV, RC and RC + TiO2 /UV are 35.3%, 49.8% and 61.5% respectively.